2011
DOI: 10.1099/vir.0.031591-0
|View full text |Cite
|
Sign up to set email alerts
|

H9 avian influenza reassortant with engineered polybasic cleavage site displays a highly pathogenic phenotype in chicken

Abstract: In the field, highly pathogenic avian influenza viruses (HPAIV) originate from low-pathogenic strains of the haemagglutinin (HA) serotypes H5 and H7 that have acquired a polybasic HA cleavage site. This observation suggests the presence of a cryptic virulence potential of H5 and H7 low-pathogenic avian influenza viruses (LPAIV). Among all other LPAIV, the H9N2 strains are of particular relevance as they have become widespread across many countries in several avian species and have been transmitted to humans. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
58
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(64 citation statements)
references
References 56 publications
5
58
0
1
Order By: Relevance
“…The involvement of such cryptic virulence determinants has been supported by results from a number of studies (8,25,29).…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…The involvement of such cryptic virulence determinants has been supported by results from a number of studies (8,25,29).…”
Section: Discussionmentioning
confidence: 56%
“…To illustrate, a H5N2 virus isolated from a broiler flock and two live bird markets in Texas in 2004 was phenotypically low pathogenic, although possessing the HA 0 cleavage site PQRKKR/ GLF and hence genotypically HPAIV (7). Discordant results between molecular and in vivo tests used to characterize virus patho- genicity were retrospectively recognized for other H5 field virus isolates (8,9), as well as non-H5/H7 viruses that had been engineered to contain polybasic HA 0 cleavage sites (25,26,27). For example Stech et al (26) showed that inserting a polybasic cleavage site identical to that of HPAI A/chicken/Italy/8/98 (H5N2) into the HA of the LPAI A/duck/Ukraine/1/63 (H3N8) virus was not sufficient to immediately transform it into a highly pathogenic virus, despite the fact that it was able to replicate in tissue culture in the absence of exogenous trypsin.…”
Section: Discussionmentioning
confidence: 99%
“…Most notably, the reassortants Hp-H2 poly , Hp-H4 poly , Hp-H8 poly , and Hp-H14 poly displayed a highly pathogenic phenotype as they led to death in all animals within 7 d after oculonasal infection. With an IVPI of 2.37, 2.79, 2.85, or 2.61, these viruses are considerably more virulent than previously reported artificial non-H5/non-H7 HPAIV like an H6 polybasic HACS mutant [IVPI 1.4 (21)] or an H9 HP reassortant [IVPI 1.23 (22)]. The lower clinical score of Hp-H14 poly after oculonasal infection, in contrast to the three other lethal reassortants, suggests that more adaptation would be required.…”
Section: Discussionmentioning
confidence: 73%
“…The lower clinical score of Hp-H14 poly after oculonasal infection, in contrast to the three other lethal reassortants, suggests that more adaptation would be required. As the IVPIs of Hp-H2 poly , Hp-H4 poly , Hp-H8 poly , and Hp-H14 poly are indistinguishable from those of genuine HPAIV, e.g., the strain A/Chicken/Pennsylvania/1370/83 (H5N2) with an IVPI of 2.37 (23) or the parental Hp-Wt with an IVPI of 2.88 (22,24), our data indicate that non-H5/H7 HA with an engineered polybasic HACS can be functionally equivalent to the HA of natural HPAIV.…”
Section: Discussionmentioning
confidence: 99%
“…Eight plasmids (pHW2000-R66-PB2, pHW2000-R66-PB1, pHW2000-R66-PA, pHW2000-R66-NP, pHW2000-R66-NA, pHW2000-R66-M, pHW2000-R66-NS, and pHW2000-R66-HA), encoding the individual viral RNA segments for influenza A virus A/chicken/Emirates/R66/2002 (H9N2) (R66) (GenBank accession numbers CY076720 to CY076727), were applied to generate recombinant viruses (68,69). To generate a mutant virus, site-directed mutagenesis was performed on the pHW2000-R66-HA plasmid using the QuikChange lightning site-directed mutagenesis kit (Agilent Technologies).…”
Section: Methodsmentioning
confidence: 99%